Peran Audit Forensik dan Audit Investigasi Terhadap Pengungkapan Fraud Dalam Suatu Perusahaan - Alya nabila; Tuti Mutia (Jurnal Riset Akuntansi, 2024)
Fraud or fraud committed by companies or individuals within the company is clearly very detrimental to the company itself, investors and the state. Forensic Audits and Investigative Audits are carried out as an effort to uncover cases. However, as time goes by, technology and systems become more sophisticated, which results in fraud perpetrators becoming more cunning in finding loopholes in covering up their fraud, therefore this research was carried out to assess how big a role Forensic Audit and Investigative Audit of Fraud Disclosure in a company.